Predictive approach to thermodynamic properties metastable CR3C carbide - Fernández Guillermet, Armando (Comisión Nacional de Energía Atómica; Argentina)
Fil: Fernández Guillermet, Armando Comisión Nacional de Energía Atómica; Argentina